2002
DOI: 10.3201/eid0808.010467
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposure to Herpesvirus B–Seropositive Macaques, Bali, Indonesia

Abstract: Herpesvirus B (Cercopithecine herpesvirus 1) has been implicated as the cause of approximately 40 cases of meningoencephalitis affecting persons in direct or indirect contact with laboratory macaques. However, the threat of herpesvirus B in nonlaboratory settings worldwide remains to be addressed. We investigated the potential for exposure to herpesvirus B in workers at a “monkey forest” (a temple that has become a tourist attraction because of its monkeys) in Bali, Indonesia. In July 2000, 105 workers at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
77
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 20 publications
6
77
0
2
Order By: Relevance
“…The BV prevalence in bred cynomolgus monkeys increased with age, and there was a very significant difference (P<0.01) in the seroprevalence of BV infection between monkeys of 2-6 years old and those > 7 years old (Table 1), which was in accordance with previous reports [1,3,6]. The likelihood of fighting, biting and coitus increases with age, and BV shed in oral or genital secretions can infect other monkeys during these activities.…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The BV prevalence in bred cynomolgus monkeys increased with age, and there was a very significant difference (P<0.01) in the seroprevalence of BV infection between monkeys of 2-6 years old and those > 7 years old (Table 1), which was in accordance with previous reports [1,3,6]. The likelihood of fighting, biting and coitus increases with age, and BV shed in oral or genital secretions can infect other monkeys during these activities.…”
supporting
confidence: 81%
“…The seroprevalence of BV infection in bred cynomolgus monkeys in Cambodia was comparable to those reported in some regions [1,3,[5][6][7], however, it was higher than that in performance monkeys (M. fascicularis) in Jakarta, Indonesia [7] and Taiwan [5] which had a prevalence of 5.3% and 11%, respectively, but lower than those reported in Brazil (71% [1]), Japan (60%, [6]) and Indonesia (81.6%, [3]). The difference in BV prevalence in different regions may be due to differences in ecological and geographical conditions, climate, as well as the conditions for monkey breeding.…”
mentioning
confidence: 68%
“…No cases of human infection have been documented despite contact between macaques and humans driving through the park, but the risk perceived by this situation warranted the action. B virus is also prevalent in free-ranging macaques native to SYNOPSIS Southeast Asia (12,37). A recent survey of workers at a Balinese Hindu temple that is a refuge for free-ranging macaques and a tourist attraction showed that contact between humans and macaques sufficient to transmit B virus commonly occurred.…”
Section: B Virus Outside the Research Settingmentioning
confidence: 99%
“…Though the local Tourist Board, through GONHS and the Gibraltar Veterinary Clinic, has erected signs that explicitly prohibit visitors from feeding macaques many visitors do offer food to the macaques, and some visitors use food to lure macaques onto their head or shoulders (Fuentes, 2006). Previous work on disease transmission between humans and macaques in Asia suggested that transmission of infectious agents both from human-to-macaque and from macaque-to-human occurred in contexts when humans and free-ranging macaques came into contact (Engel et al, 2002;Jones-Engel et al, 2001,2005a. It is hypothesized that macaque bites and scratches as well as mucosal contact with body fluids can lead to crossspecies transmission.…”
Section: Introductionmentioning
confidence: 99%